2020
DOI: 10.1001/jamanetworkopen.2020.10511
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pediatrician Awareness and Implementation of the Addendum Guidelines for the Prevention of Peanut Allergy in the United States

Abstract: IMPORTANCE The 2017 Addendum Guidelines for the Prevention of Peanut Allergy in the United States recommend that pediatricians assess infant peanut allergy risk and introduce peanut in the diet at age 4 to 6 months. Early introduction has the potential to prevent peanut allergy development. OBJECTIVES To measure the rates of guideline awareness and implementation and to identify barriers to and factors associated with implementation among US pediatricians. DESIGN, SETTING, AND PARTICIPANTS This population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…The greatest barriers to Guidelines implementation that the survey identified were parental concerns about allergic reactions, parents who were not interested in early feeding, and lack of referrals. In both this survey of allergists and our survey of US pediatricians, 9 parental concern about allergic reactions was the most frequently identified barrier to implementation, a finding that is not surprising at this early stage of Guidelines implementation and consistent with surveys of parental acceptance of the early introduction of peanut-containing-foods. 11,12 Lai and Sicherer 12 reported that the most common physicianperceived implementation barrier was parental acceptance, and the most common parent-identified barriers were fear of reaction and choking, although 90% of parents indicated comfort with early peanut introduction when answering yes or no.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The greatest barriers to Guidelines implementation that the survey identified were parental concerns about allergic reactions, parents who were not interested in early feeding, and lack of referrals. In both this survey of allergists and our survey of US pediatricians, 9 parental concern about allergic reactions was the most frequently identified barrier to implementation, a finding that is not surprising at this early stage of Guidelines implementation and consistent with surveys of parental acceptance of the early introduction of peanut-containing-foods. 11,12 Lai and Sicherer 12 reported that the most common physicianperceived implementation barrier was parental acceptance, and the most common parent-identified barriers were fear of reaction and choking, although 90% of parents indicated comfort with early peanut introduction when answering yes or no.…”
Section: Discussionsupporting
confidence: 74%
“…In a parallel survey we conducted on US pediatricians, the need for additional educational efforts among pediatricians was clearly identified. 9 One limitation of this study is the survey response rate. Among AAAAI members, 29% answered at least 1 question in the survey and 24% completed the survey.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The 2000 AAP policy 167 recommended avoidance of allergenic foods for breastfeeding mothers and delayed introducing allergenic foods to infants to prevent FA was based on expert opinion informed by a limited number of low quality studies. 168 These guidelines influenced infant feeding practices for almost 20 years, 169 while FA only continued to increase, rather than decrease. These guidelines were reversed in 2008, but not replaced with comprehensive guidelines, only limited recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Recent publications have highlighted clinical practice deficits, including the inappropriate treatment of anaphylaxis 4 and the lack of implementation of peanut feeding guidelines by primary care clinicians. 5 Although pediatricians are frontline providers for infants (<12 months) and toddlers (12-35 months) with FA, the Accreditation Council for Graduate Medical Education (ACGME) does not require a pediatric allergy curriculum as part of pediatric residency training.…”
mentioning
confidence: 99%